Body Representation Alterations in Patients with Unilateral Brain Damage. (5th February 2022) - Raimo, Simona; Boccia, Maddalena; Di Vita, Antonella; Iona, Teresa; Cropano, Maria; Ammendolia, Antonio; Colao, Roberto; Angelillo, Valentina; Maiorino, Antonio; Guariglia, Cecilia; Grossi, Dario; Palermo, Liana
Abstract: Objective: Systematic studies about the impact of unilateral brain damage on the different body representations (body schema, body structural representation, and body semantics) are still rare. Aim of this study was to evaluate body representation deficits in a relatively large sample of patients with unilateral brain damage and to investigate the impact of right or left brain damage on body representations (BRs), independently from deficits in other cognitive processes. Method: Sixty-four patients with unilateral stroke (22 with left brain damage, LBD; 31 with right brain damage without neglect, RBD-N; 11 with right brain damage with neglect, RBD+N) and 41 healthy individuals underwent a specific battery including BR as well as control tasks. Results: In more than a third of the sample, selective (37.5%) and pure (31%) deficits of BR were presented and equally distributed among the different BRs (˜10% for each representation), with selective (27.2%) and pure (22.7%) body schema deficit mainly presented after left brain damage. As a group, patients with unilateral brain damage, independently of the side of lesion (LBD, RBD-N, RBD+N), had significantly worse performance on body structural representation with respect to healthy individuals, whereas LBD had numerically worse performance on body schema with respect to healthy individuals and RBD-N. No significant differences among groups were found on body semantics. Conclusion: BR deficits are not a rare consequence of unilateral brain damage and are independent of a more general cognitive dysfunction. Accordingly, the need for an accurate assessment and specific neuropsychological training in clinical settings is discussed.